Guatemala : Request for Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper examines Guatemala's Request for a Stand-By Arrangement (SBA). The authorities are requesting a 12-month SBA in an amount equivalent to SDR 84 million (40 percent of quota) to support an economic program aimed at reducing the fiscal deficit and restructuring the financial system, while sustaining higher outlays on social and basic infrastructure as called for by the Peace Accords. The program assumes an acceleration of real GDP growth to 2.25 percent and a reduction in inflation to a 4-6 percent range.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet